Usability Analysis on the Multitap ABC Standard Keypad and QWERTY Keypad on Mobile Phones based on Time, Errors and Satisfaction Scale - Sigit Rahmat Rizalmi; Noni Oktiana Setiowati; Muhamad Imron Zamzani (Universitas Katolik Musi Charitas, 2021)
The use of mobile phone keypads to exchange messages has become a daily activity at this time. Keypad is one of the most widely used input devices compared to other input devices. When typing on a cell phone, users will usually try to type correctly and quickly. The improvements of mobile phone products include a wide variety of physical designs. Keyboard or keypad is one part that does not escape the development. The keypad on the phone is an arrangement of keys containing numbers, letters of alphabet, punctuation marks and certain symbols that are needed. In general, there are two types of cell phone keypads on the market, namely the alphanumeric keypad on the Multitap ABC Standard keypad and the QWERTY keypad. Each type of keypad has a different arrangement of letters and different methods of use. With the development of variations in keypad designs, this study aims to compare the design of the Multitap ABC Standard keypad with the QWERTY keypad on Xiaomi cellphones in order to find usability problems based on time, error and satisfaction scale. The results showed that the usability of the QWERTY keypad is better than the standard ABC multitap keypad in terms of time and error. Based on the time to complete the task, the users completed the task faster using the QWERTY keypad compared to the Multitap ABC Standard keypad. Based on the error rate in completing the task, the users made less errors using the QWERTY keypad compared to the Multitap ABC Standard keypad. Based on the level of satisfaction in using the keypad type, there is no significant difference between two types of the keypads